Exploring the impact of daily food habit and modification of lifestyle for boosting immunity against COVID-19 - Rashni Agarwala; Israt Jahan Maria; Promi Dewan; Md. Mafizur Rahman; Zubaer Hosen; Md. Adnan (Heliyon, 2022)
The lockdown crisis due to novel coronavirus (COVID-19) mainly affected people who live under economic despair. Since boosting the immune system against the virus depends on a variety of food intake and lifestyle approaches; hence, it is crucial to know how daily food habits and lifestyle modification protect from pathogenic viral infections. This study focused on the benefit of plant-based foods, functional foods and the modified lifestyle which enhance the immunity of all aged groups against COVID-19 in Bangladesh. An online close-ended randomly selected structured multiple-choice questionnaire survey was conducted for people of different parts of Bangladesh (n = 161; male 51.55%, female 48.45%). The total percentage was counted for all variables. We found that plant-based foods, functional foods, and physical exercise played a vital role in enhancing people's immunity to control COVID-19. Plant-based micronutrients, nutraceuticals and antioxidants mainly took part to boost the immune system against the virus. Furthermore, physical activity had a vital role in improving people's immunity to manage COVID-19. Literature suggested that food habits, body immunity, awareness, stress and weight variation were affected by the COVID-19 pandemic. The vaccine or proper medication of COVID-19 still remains in an enigma. In this situation, boosting immunity to combat Coronavirus is the only way to survive.